Positioning construction businesses on an 'evolution‒innovation' continuum: conceptualization of the 'equivocal zone'. Issue 3 (2nd July 2016) - Holt, Gary D.; Goulding, Jack S.
Abstract : The concepts of 'business evolution' and 'innovative business endeavour' are contrasted as bipolar extremes on a theoretical continuum: first in the context of organizations generally and second for construction businesses specifically. This highlights what the authors define as an 'equivocal zone' (EZ), which occupies a wide section of the continuum and is positioned approximately equidistant from its extremes. Cogent representation of the zone is based on literature synthesis, emphasizing contemporary and emergent viewpoints in the field; while its conceptualization is achieved using descriptive and graphical models. The study argues that within the EZ, definitions of organizational innovation often become blurred and that the EZ characterizes most construction organizations on the evolution‒innovation continuum. The EZ is a new theoretical concept derived solely from this study.